2018
DOI: 10.2478/alife-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Nutrient Uptake Improvement of Chickpea (Cicer Arietinum L.) by Dressing Fertilization and Nitrogen Doses

Abstract: The present investigation aimed to understand the effects of dressing fertilizers and different nitrogen (N) doses on yield and nutrient uptake of chickpea (Cicer arietinum L.) plant. The study has been carried out with three repetitions under the greenhouse conditions. Nitrogen doses were; 0 kg N ha-1, 30 kg N ha-1, 60 kg N ha-1, 90 kg N ha-1 and 120 kg N ha-1 (in CaNO3.4H2O form) and dressing fertilizers were applied as 40 kg N ha-1. The results indicated that the dressing fertilizer application significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…In 2019 year, bacteria fertilizer treatment had high effect on all cultivars except Gokce, and the effect of bacteria treatment is similar to or higher than the control group (Table 2). Demirbas et al (2018) reported that the greatest dry matter production was obtained from bacteria and supply N treatment. Some researchers have reported that nitrogen fertilizer treatments significantly were increase stem weight (Bicer, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In 2019 year, bacteria fertilizer treatment had high effect on all cultivars except Gokce, and the effect of bacteria treatment is similar to or higher than the control group (Table 2). Demirbas et al (2018) reported that the greatest dry matter production was obtained from bacteria and supply N treatment. Some researchers have reported that nitrogen fertilizer treatments significantly were increase stem weight (Bicer, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In saline soils, the preponderance of nonessential elements makes the essential elements unavailable (Fageria et al, 2011). The nitrogen uptake can be enhanced by dressing fertilization in chickpea (Ahmet et al, 2018). Inoculation with Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Demirbaş ve ark. farklı dozda azotlu gübreleme ve bakteri uygulamasının nohudun özelliklerine etkisini araştırdıkları saksı çalışmasında, en yüksek kök kuru madde miktarını hektara 120 kg N uygulanan ve bakteri inokulasyonu yapılan işlemden elde edildiğini, gübresiz ve bakteri uygulanmayan işlemler hariç nohudun kök kuru madde üretiminin N dozunun artışı ile arttığını belirlemişlerdir [16]. Çalışmamızda biyolojik verimi ifade edecek bitki ağırlığı gübre uygulamalarından istatistiki olarak etkilenirken kök ve gövde kuru madde miktarları arasında farklılık olmadığı sonucuna varılmıştır (Tablo3).…”
Section: Materyal Ve Yöntemunclassified